Ghana : Request for a Three-Year Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2015)
EXECUTIVE SUMMARY Context. The emergence of large fiscal and external imbalances in recent years, which led to a slowdown in growth, is putting Ghana's medium-term prospects at risk. The Government's efforts to achieve fiscal consolidation since mid-2013 have been undermined by policy slippages, external shocks and rising interest cost. Until mid- 2014, the net international reserves position had further weakened and the exchange rate depreciated sharply, fueling inflationary pressures. The situation has stabilized on the back of the Eurobond issued in September and a short-term loan contracted by the Cocoa Board, but public debt continued to rise at an unsustainable pace. Extended Credit Facility Arrangement (ECF). The Ghanaian authorities have requested a three-year arrangement under the ECF in an amount of SDR 664.20 million (180 percent of quota) in support of their medium-term economic reform program. Program Framework. The authorities' three year ECF-supported program, anchored on their second Ghana Shared Growth and Development Agenda (GSGDA II), aims at a sizeable and frontloaded fiscal adjustment to restore debt sustainability, rebuild external buffers, and eliminate fiscal dominance of monetary policy, while safeguarding financial sector stability. It focuses on: ? Substantially strengthening the fiscal position by mobilizing additional revenues, restraining the wage bill and other primary spending, while making space for priority spending. The government is also taking additional adjustment measures to help offset lower-than-budgeted oil revenue. A prudent borrowing policy will complement fiscal consolidation efforts to restore debt sustainability. ? Accelerating the reform agenda: strengthening public financial management and expenditure controls, in particular cleaning-up the payroll and enhancing wage bill control; improving revenue collection through tax policy and tax administration reforms; restoring the effectiveness of the inflation-targeting (IT) framework by eliminating fiscal dominance and enhancing monetary policy operations. Risks. Risks to the program include delayed or partial implementation of policies, including next year in the run-up to elections, a slower growth recovery if the electricity crisis is not addressed quickly, and additional negative commodity price shocks. Staff supports the authorities' request for IMF support. Forceful and sustained implementation of the program will be essential to address macroeconomic imbalances.